Peran Orang Tua Dalam Mengawasi Tontonan Film Pada Anak - Hayani Wulandari; Kholic Kholic (Peneliti.net, 2023)
Animated films are very interesting for children with the support of technological advances, we skip a lot of animated films, the role of parents in supervising children's viewing sometimes parents still ignore it, we skip a lot of children who imitate scenes of animated films children like which causes children to experience loss. This study aims to find out how the role of parents in supervising children in watching children's animated films. The research method used is literature study. Sources of library research in this study were taken from online news articles, printed books, and scientific journals. The results of the study show that the role of parents in supervising children in watching animated films is very important and needed by children, so that children do not receive the negative effects of animated films.